Fascist Italy and nazi Germany : the 'fascist' style of rule - De Grand, Alexander J. (London : Routledge, 1995)
Bibliotheek François Vercammen
Engels
Monografie
Keywords: fascisme; Nazisme; Italië; Duitsland